Optional learning opportunities: who seizes them and what are the learning outcomes? - Seifried, Eva; Eckert, Christine; Spinath, Birgit (Teaching of psychology, 2018)
The effects of offering and seizing optional learning opportunities rarely have been investigated. Thus, university instructors have no basis on which to decide whether offering optional learning opportunities to their students would be worth the effort and which students would seize and benefit from them. To target these questions, we designed a teaching−learning format in which we offered psychology undergraduates optional learning opportunities throughout the semester. We investigated the cognitive and motivational prerequisites of N=108 students who seized versus forwent the learning opportunities and compared their learning outcomes both with and without controlling for prerequisites. Concerning prerequisites, we found that students who seized the learning opportunities had a better school grade point average, whereas they did not differ from the students who did not seize the learning opportunities regarding their prior knowledge or their motivational prerequisites and outcomes. Students who seized learning opportunities had better performance outcomes, even after initial prerequisites or time spent learning were controlled for. We conclude that there is a benefit of seizing optional learning opportunities for students, and therefore, instructors should enable their students to take this chance.